Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex]3\frac{1}{4}*(-2\frac{3}{5})= \frac{13}{4}*(-\frac{13}{5})=-\frac{13*13}{4*5}=-\frac{169}{20}=-8\frac{9}{20} [/tex]
[tex]3\frac{3}{4}\cdot(-2\frac{3}{5})=\frac{3\cdot4+1}{4}\cdot\left(-\frac{2\cdot5+3}{5}\right)=\frac{13}{4}\cdot\left(-\frac{13}{5}\right)=-\frac{13\cdot13}{4\cdot5}=-\frac{169}{20}=-8\frac{9}{20}\\\\\\Answer:A[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.